A bibliometric analysis of the studies in high-altitude induced sleep disturbances and cognitive impairment research - Zhang, Jiexin; Tang, Songyuan; Chen, Chao; Jiang, Hezhong; Liao, Hai; Liu, Huawei; Wang, Li; Chen, Xin (Frontiers in Physiology, 2023)
Background: The two main symptoms at high altitude, sleep abnormalities and cognitive impairments, interact with each other. These two dysfunctions are also closely related to systemic multisystem diseases, including cerebrovascular diseases, psychiatric disorders, and immune regulatory diseases. Purpose: To systematically analyze and visualize research on sleep disturbances and cognitive impairment at high altitudes using a bibliometrics method, and to determine future research directions by analyzing research trends and the latest hotspots. Methods: Publications from 1990 to 2022 on sleep disturbances and cognitive impairment at high altitudes were retrieved from the Web of Science. Using the R Bibliometrix software and Microsoft Excel, all data were examined statistically and qualitatively. For network visualization, the data were later exported into VOSviewer 1.6.17 and CiteSpace 6.1.R6. Results: A total of 487 articles in this area were published from 1990 to 2022. In this period, there was an overall increase in the number of publications. The United States has shown considerable importance in this sector. Bloch Konrad E was the most prolific and valuable author. The most prolific journal was High Altitude Medicine & Biology, and it has been the first choice for publishing in this field in recent years. Analysis of keyword co-occurrences suggested that research interest in the clinical manifestations of sleep disturbances and cognitive impairment caused by altitude hypoxia was mainly focused on "acute mountain-sickness", "insomnia", "apnea syndrome", "depression", "anxiety", ''Cheyne-strokes respiration", and " pulmonary hypertension". The mechanisms of disease development related to "oxidative stress", "inflammation", "hippocampus", "prefrontal cortex", "neurodegeneration", and "spatial memory" in the brain have been the focus of recent research. According to burst detection analysis, "mood" and "memory impairment", as terms with high strength, are expected to remain hot topics in the coming years. High-altitude-induced pulmonary hypertension is also in the emerging stage of research, and the treatments will continue to receive attention in the future. Conclusion: More attention is being focused on sleep disturbances and cognitive impairment at high altitudes. This work will serve as a useful reference for the clinical development of treatments for sleep disturbances and cognitive impairment induced by hypobaric hypoxia at high altitudes.